2016
DOI: 10.15277/bjd.2016.095
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and pruritus

Abstract: Pruritus is often reported to be associated with diabetes mellitus although this remains controversial. Careful historytaking and examination are key to establishing the cause of itching in a patient with diabetes after excluding local cutaneous disease or an underlying lymphoma. Options for management of this distressing condition include emollients, topical antipruritic agents (e.g. calamine, menthol, capsaicin, corticosteroids, calcineurin inhibitors or local anaesthetics), systemic antipruritic agents (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
2
14
0
1
Order By: Relevance
“…21 Metabolic abnormalities, autonomic dysfunction, anhydrosis and diabetic neuropathy all may contribute to generalised pruritus. 20 The prevalence of iron deficiency anaemia was 11% according to our study. In that 3% of patients were associated with systemic diseases like hypothyroidism, diabetes and chronic renal disease.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…21 Metabolic abnormalities, autonomic dysfunction, anhydrosis and diabetic neuropathy all may contribute to generalised pruritus. 20 The prevalence of iron deficiency anaemia was 11% according to our study. In that 3% of patients were associated with systemic diseases like hypothyroidism, diabetes and chronic renal disease.…”
Section: Discussionsupporting
confidence: 52%
“…19 Pruritus is often associated with diabetes mellitus although this is remaining controversial. 20 As per Al-Mutairi et al study the prevalence of pruritus among diabetic patients was 49%. A study in elderly subject showed diabetes to be a statistically significant predictor of pruritus.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The mean AP intensity evaluated with VAS (4.8 ± 1.9 points) was lower in comparison with pruritus observed in common dermatoses, such as atopic dermatitis (7.9 ± 2.2 points) (13), chronic urticaria (7.5 ± 1.8 points) (24) or lichen planus (6.5 ± 2.7 points) (25). However, with regard to other internal diseases, such as uraemic pruritus (4.1 ± 2.0 points) (26) or diabetes mellitus (4.7 ± 2.8 points) (27), the severity of AP appears to be comparable. Considering the assessments conducted with 4-item Itch Questionnaire, in opposition to other diseases presenting similar symptoms, such as atopic dermatitis (14.0 ± 4.4 points) (13) or uraemic pruritus (8.2 ± 4.5 points) (15), the mean results for AP were somewhat lower (6.0 ± 2.9 points).…”
Section: Discussionmentioning
confidence: 99%